What Drives Interest Rate Spreads in Pacific Island Countries? : An Empirical Investigation - Jamaludin, Fazurin (IMF Working Papers; Working Paper ;, 2015)
Growth has been sluggish in Pacific island countries (PICs). High cost of credit is likely one of the reasons. While the small scale, geographic dispersion, and vulnerability to shocks increase the cost and risk of credit in this country group, there is considerable variability in interest rate spreads both across countries and over time. This paper examines the determinants of lending rates and interest rate spreads in a panel of six PICs, extending the literature that was largely descriptive in nature or focused on a single country. Our results are in line with economic theory. We find that the size of the economy is negatively correlated with spreads, confirming the importance of scale. Inflation appears to have only marginal impact on spreads. High loan loss provisions and nonperforming loans increase the cost of credit. So does banking system concentration. Higher institutional quality is associated with lower spreads.